Leads dislodged into the pulmonary vascular bed in patients with cardiac implantable electronic devices - Polewczyk, Maciej; Jacheć, Wojciech; Polewczyk, Aneta M.; Polewczyk, Anna; Czajkowski, Marek; Kutarski, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Spontaneous lead dislodgement into the pulmonary circulation is a rare complication of permanent pacing with unproven harmfulness and an indication of controversial class for transvenous lead extraction (TLE). Aim: To assess TLE safety in patients with leads dislodged into the pulmonary artery. Material and methods: A retrospective analysis of a 9-year-old database of transvenous lead extraction procedures comprising 1767 TLEs was carried out, including a group of 19 (1.1%) patients with leads dislodged into the pulmonary artery (LDPA). Results: Under univariate analysis the factors that increased the likelihood of the presence of an electrode in the pulmonary artery were mean lead dwelling time (increase of risk by 9% per year), total number of leads in the heart before TLE (increase of risk by 66% for one lead) and the number of abandoned leads (increase of risk by 119%). The presence of LDPA was associated with frequent occurrence of intracardiac lead abrasion (increase by 316%) and isolated lead-related infective endocarditis (LRIE) (increase by 500%). There were no statistically significant differences in clinical (p = 0.3), procedural (p = 0.94) or radiological (p = 0.31) success rates in compared (LDPA and non-LDPA) groups. Long-term mortality after TLE was comparable in both groups. Conclusions : As the effectiveness and safety of TLE in patients with LDPA are comparable to those in standard TLE procedures, in our opinion, such patients should be considered TLE candidates.